In Vitro Anti- Malassezia Activity of Castanea crenata Shell and Oil-Soluble Glycyrrhiza Extracts - Han, Song Hee; Hur, Min Seok; Kim, Min Jung; Jung, Won Hee; Park, Minji; Kim, Jeong Hwan; Shin, Hong Ju; Choe, Yong Beom; Ahn, Kyu Joong; Lee, Yang Won (Annals of dermatology, 2017)
A new shampoo with anti- properties obtained from various plants is required to provide seborrheic dermatitis patients with a wider range of treatment options. The aim of this study was to obtain susceptibility profiles of and , the most important pathogenic organisms in the development of seborrheic dermatitis, to the plant extracts used in commercial anti-dandruff shampoos. Minimal inhibitory concentrations (MICs) were determined for eight candidate plant extracts and two plant-derived natural products diluted with Leeming and Notman medium to final concentrations of 0.016 to 1 mg/ml. shell, leaf, and oil-soluble extracts presented relatively low MIC values (≤0.5 mg/ml) against both strains. The shell and oil-soluble extracts demonstrated especially high activity, suggesting their potential use in the treatment of seborrheic dermatitis. The extracts also showed fungistatic activity against other common facultative pathogenic yeasts, and . shell and oil-soluble extracts could potentially be used as active ingredients in anti-seborrheic and anti-dandruff shampoo formulations. They could be helpful for repeated treatments and regular prophylaxis of scalp seborrheic dermatitis.